Recent Watermarking Patents of Digimarc Corporation: The Period between March ’12 - June ‘12 - Geetha, S.; Sindhu, Siva S.S. (Recent Patents on Computer Science, 2013)
Digital watermarking technology remains an active area of study and development by a number of companies and institutions since mid ‘90s. This area fetches more and more attention as one of the key technology components for copyright protection, content management, and copy control of digital contents. This paper discusses the different patents procured by Digimarc Corporation during the period between March 2012 and June 2012. The basic principles, the core characteristics and the uniqueness of each patent are touched upon followed by a discussion on the most suitable application each patent serves. The paper is organized around the application types namely - content identification and management, content protection of image/video content, image quality control, document and image security, authentication of content and objects. The challenges and the potential future scopes of the field are also pointed out.
Keywords: patent